CRIMINAL POLICIES BASED ON RELIGIOUS VALUES IN TACKLING CYBER ADULTERY - Any Ismayawati (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2018)
Research on crime-based policies of religious values in tackling cyber adultery aims to determine whether cyber adultery can be used as criminal tyindak as well as to know what basis can be used to criminalize cyber adultery. For this research to achieve the desired result, this research uses qualitative research tradition, with constructivism paradigm, with socio legal approach and data analysis using hermeneutic approach method, phenomenology, comparison and policy. The results show that cyber adultery has become a very disturbing problem for society, because the impact of adultery causes disharmony of household, divorce and even moral degradation of the nation. Cyber adultery poses various problems in society, but there is no rule / law that specifically prohibits cyber adultery so difficult to overcome. Based on the results of the research can be concluded that cyber adultery can be made criminal act because it is not in accordance with the collective values embraced by the Indonesian nation and Causes losses matriil and morale for the nation of Indonesia. The foundation that can be used to make cyber adultery as a crime is the religious values that exist in Indonesia